FREE HEIR SEMINARS AND CONSULTATIONS DYNAMICS AND SOLUTIONS IN THE DIVISION OF ISLAMIC INHERITANCE LAW AND CIVIL INHERITANCE LAW - Muhammad Isa; Dody Yarli (Tamkin Jurnal Pemberdayaan Tazkia, 2026)
This activity was carried out to answer the needs of the community regarding inheritance problems that occur, especially in Indonesia. Where inheritance is often a source of family conflict. This seminar is carried out using an online method which is open to the public free of charge. Apart from the seminar, participants were given free inheritance consultation sessions to experts. The results of this activity were quite satisfactory, where the participants were very enthusiastic and asked for a personal consultation session after the seminar. On the other hand, it is known that there is a lot of concern among the general public regarding inheritance problems that occur in their families. Through this program, people who contribute get answers to the problems they experience.